Emotion, subjectivity, memory and mental health. - Bertolín-Guillén, José Manuel (2022)
Clinical psychology and psychiatry use different strategies to modify inadequate, maladjusted or psychopathological emotional and behavioral schemas. This study is based on related relevant international scientific literature, an original narrative qualitative research with integrating, aggregational and interpretative components. The physiological response, so linked to genomics, and the experience of thoughts and feelings are fundamental for emotionality. Affective logic and work memory express well that preferences and intentions generally decide and then rationality, explains. Thanks to the role of terminal stria, the subcortical amygdala structure is able to trigger any type of emotional response. In short, truth or certainty in multiple environments will only be an opinion and not something unquestionable. The anatomophysiology, beliefs, culture and personal attitudes are interrelated and influence themselves mutually on a continuous basis.